Social Research about Online Crime: Global Range of Topics and a Systematic Analysis of Research in Lithuania - Šupa, Maryja (Kriminologijos studijos, 2021)
Social research about online crime is a multi-disciplinary field addressing a wide array of topics since its inception in the 1980s. Based on a broad review of state-of-the-art literature and gaps identified in review publications (Holt, Bossler 2014; Stratton, Powell, Cameron 2017; Maimon, Louderback 2019, and others), in this paper I outline 41 key topic in social research about online crime, classified into four broad categories: 1) research focusing on specific types of online crime, 2) research about perpetrators, victims, and law enforcement, 3) research about online crime discourses and public perceptions, 4) research putting the local and global specifics of online crime into perspective. Based on the topic map, I undertook a systematic review of literature on research about online crime published in Lithuania from the empirical social scientific perspective. The results show that very few such studies are carried out in Lithuania. From 2004 to 2020, 26 publications have been found in total. 10 of them were theoretical briefs, while 16 were based on empirical data. Out of the 41 key topic, 14 were covered in the publications, while 29 or roughly two thirds remained unaddressed. The dominant contributors were legal scholars writing about the social aspects of online crime across a variety of topics, and mostly focusing on specific crime types. The most developed topic was cyberbullying, with contributions by scholars mostly from the fields of psychology and education. To fill in these glaring gaps, it is vital to develop this field of research with an emphasis on both wider and deeper research agendas, complex, valid and reliable research data and critical theoretical approaches, inviting systematic contributions from criminology, sociology, communication and media studies, and political science.